Living in a Legal Limbo: Mechanisms to “Fix” The Legal and Social Positions of Unregistered Children in Indonesia - Horii, Hoko; Wirastri, Theresia Dyah (UI Scholars Hub, 2022)
This paper examines the reasons and consequences of a lacking birth-registration in Indonesia, as well as the mechanisms to ‘fix’ it. In order to avoid the legal and social consequences of the lack of registration, creative and ad-hoc solutions are crafted – not only by the individual families who face the problem, but also by their community, including local and state actors who are involved in the mechanisms and paperwork. These mechanisms exist also because of state’s reluctance to enforce regulation related to unregistered marriage and children born into unregistered marriage as these matters are religiously and culturally delicate. We argue that the state facilitates all types of unregistered marriages, which results in blurring legal parameters of marriage. This leads unregistered children to be living in a legal limbo: their legal status and attached rights remain unclear, not being fully ensured of their rights to public services, inheritance, and child maintenance.